Isatin: a privileged scaffold for the design of carbonic anhydrase inhibitors - Claudia Melis; Rita Meleddu; Andrea Angeli; Simona Distinto; Giulia Bianco; Clemente Capasso; Filippo Cottiglia; Rossella Angius; Claudiu T. Supuran; Elias Maccioni (Taylor & Francis Group, 2017)
The isatin scaffold is the constitutive fragment of several natural and synthetic bioactive molecules. Albeit several benzene sulphonamide-based carbonic anhydrase inhibitors (CAIs) have been reported, only recently isatin benzene sulphonamides have been studied and proposed as CAIs. In this study we have designed, synthesised, and evaluated the biological activity of a series of differently substituted isatin-based benzene sulphonamides which have been designed for the inhibition of carbonic anhydrase isoforms. The activity of all the synthesised compounds was evaluated towards human carbonic anhydrase I, II, IX, and XII isozymes. Our results indicate that the nature and position of substituents on the isatin ring can modulate both activity and isozyme selectivity.